Mobile Off-grid Achitecture. A potential tool for the resilience of rural communities in the event of natural disasters - Shota Tajima; Satoko Nasu (Agathón)
The paper illustrates a study conducted for the town of Nagara in Japan to test the use of mobile off-grid architecture (MOA) in support of the resilience that rural communities are expected to acquire by 2050. In order to cope with the effects of climate change that have severely affected human lives and natural ecosystems, to counter population ageing, migration to larger urban centres and the inefficiency of outdated infrastructure, Japan’s rural areas need to increase their resilience to ensure human continuity in their territories. In this context, the authors propose a MOA solution developed on the basis of literature review and a questionnaire to manufactures and local government, using a deductive approach to determine its feasibility. The results of the experimental project suggest that the MOA could be used for various purposes, including social education and rural community development, although the feasibility has yet to be confirmed in relation to the critical issues represented by the weight and cost of mobile architecture.